Use of Autotransplantation of Wisdom Tooth in Managing Oroantral Communication - Kinga Trepanowska; Michał Armatys; Bartosz Bielecki-Kowalski; Anna Dudko; Sebastian Kłosek (Journal of Clinical Medicine, 2026)
Oroantral communication (OAC) is a known complication of maxillary tooth extraction that may lead to issues such as oroantral fistula formation and chronic maxillary sinus disease if left untreated. Although several surgical techniques for OAC closure have been described in the existing research, autotransplantation of a third molar represents a rarely reported alternative. This method not only allows for the closure of OAC but also restores masticatory function and may be an alternative to implantation. This review evaluates the available literature on third molar autotransplantation for OAC management, with particular attention to donor tooth selection, recipient-site preparation, surgical techniques, postoperative management, and clinical outcomes. The currently available literature on the mentioned topic is limited and consists predominantly of case reports and small clinical series. Nevertheless, published cases indicate that third molar autotransplantation may provide successful OAC closure and functional tooth replacement in appropriately selected cases. Significant heterogeneity and incomplete reporting of surgical and postoperative procedures, however, limit the strength of the available evidence. In this article, we propose a clinically oriented algorithm to facilitate decision-making in selected cases. This algorithm should be regarded as an expert-based framework requiring prospective clinical validation rather than an established standard of care.